Pengaruh Edukasi Terapi Non Farmakologi pada Pasien Hipertensi - Fadillah, Raisa Noer; Rindarwati, Asti Yunia (Lembaga Penelitian dan Pengabdian Masyarakat, Sekolah Tinggi Ilmu Kesehatan Salsabila Serang, 2023)
Hypertension, also known as high blood pressure, is a condition where a person's blood pressure is ? 140 mmHg (systolic) and/or ? 90 mmHg (WHO, 2019). Hypertension is often referred to as the